HAPPINESS ANALYSIS OF LIBYANS PEOPLE BASED ON TWITTER DATA USING ARTIFICAL NEURAL NETWORK - khaled jemah basher; Imam Much Ibnu Subroto; Arief Marwanto; Muhammad Qomaruddin (Journal of Telematics and Informatics, 2020)
Information technology is always developing and has very rapid growth. The internet has become a very important online communication tool for many people today. Nowadays people tend to prefer anything that is practical, faster, and flexible. Social networking services have become a simple and universal concept in the internet environment. Purpose of this study are: To analyse happiness of Libyans people based on Twitter data using artificial neural network. This study is an analytical study of secondary data processing obtained without direct field experiments. MTE (Magister program of Electrical Engineering) UNISSULA must have experiment. This study is an analytical study of data based on social media specifically using twitter data. The result of this study is Libyan feel they write down their feelings when happy rather than unhappy. Social media has become an important part of modern life, and Twitter is again a center of focus in recent events. Whatever your opinion of social media these days, there is no denying it is now an integral part of our digital life. Twitter is a good starting point for social media analysis because people openly share their opinions to general public. This is very different from Facebook where social interactions are often private. In this paper, we propose a ANN model for Twitter opinion mining prediction and classification approach. Also, we used the ANN model for Twitter Opinion abstraction and visualization scheme. The main contribution of this work is to propose such a new visualization model for Twitter mood prediction based on ANN  approach